Analysis of Students to Follow Computer Extracurricular Activities using Fuzzy Logic Method - Loneli Costaner; Guntoro Guntoro; Lisnawita Lisnawita (Sistemasi: Jurnal Sistem Informasi, 2023)
An educational institution will carry out activities for the development of human resources. In improving good human resources, additional lessons are needed to increase students' skills, especially in the computer field. The current obstacle is that schools have difficulty measuring students' interest in participating in computer extracurricular, as a result the development of computer hardware needs is hampered. This study aims to provide knowledge to schools to find out what percentage of students are interested in learning computers. The method used is a Likert scale and fuzzy logic by measuring four variables of student feelings, student attention, student interest and student involvement. Measurement of student interest by compiling a questionnaire filled in by students and students there are 14 questions with a choice of each question 5 answer choices, obtained an average weight on the Likert scale variable feeling 74.0%, attention 76.5%, interest 75.7% and the involvement of 78.0% of the weight was tested with fuzzy inference with a firmness value of 38, where the value is included in the output domain not interested. By measuring student interest, it is hoped that it will be useful for institutions to consider implementing computer extracurricular.